Team Retreats for Interprofessional Trainees and Clinic Staff: Accelerating the Development of High-Functioning Teams - Shalini Patel; Bridget C. O'Brien; Maya Dulay; Gillian Earnest; Rebecca L. Shunk (Association of American Medical Colleges, 2018)
Introduction Teams are critical to managing the health care needs of patients with part-time trainee providers. High-functioning teams require trusting relationships among trainees and staff and opportunities to learn and practice skills together. Irregular trainee schedules, time-limited training programs, and lack of protected time for team development during clinic can hinder development of high-functioning teams. Methods To provide time for team development, we created an annual half-day team retreat for interprofessional trainees and staff at three San Francisco Veterans Affairs primary care clinics. We used principles of high-functioning teams and relationship-centered communication to develop retreat content, then trained interprofessional faculty members to facilitate and role-model this content. Retreat objectives and content focused on building relationships, establishing team goals, clarifying roles, and learning communication skills. Postretreat surveys and qualitative content analysis of comments and team goals evaluated retreat objectives and opportunities for improvement. Results Between 2011 and 2017, 16 team retreats were attended by 232 interprofessional trainees and 77 unique staff (some attended multiple times). Thirty-seven faculty facilitated. Most participants strongly agreed that they knew their team members better personally and professionally after the retreat (M = 4.7 out of 5, n = 368); 78% of teams (n = 65) submitted SMART goals addressing high-functioning teams. Participants' comments consistently reflected the benefits of protected time for team building. Discussion This team retreat supports team development among trainees and staff on primary care teams by promoting relationship building, role clarity, communication, and team processes. It can be valuable for all interprofessional participants.